Connotative Implications of Phonostylistic Repetition in Linguistics (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
In this article, the author examines connotative implications of phonostylistic repetition in linguistics and both features of phonetic repetition, namely their conjunctive meanings in the case of English and Uzbek languages, using pure visual phonological method with respect to artistic visualization, alliteration and sound repetition and also the phenomenon of alliteration in repetitive languages is of phonostilistic significance. In the poetic speech, the repeated pronunciation and spelling of all of the same consonants, a number of additional meanings, such as melody, music, emotional painting, charm, satisfaction, pleasure, development of thinking, attitudes, and pleasure.